Konsep HAM dalam Pemikiran Hukum Islam Modern (Telaah atas Pemikikiran Abdullahi Ahmed An-Na’im) - Khotimah, Khusnul (Al-Manahij: Jurnal Kajian Hukum Islam, 2008)
Abdullahi Ahmed An-Na'im tried to confront the secularism and fundamentalism. He used naskh to pay more attention on humanism, equity and freedom. Eventhough there are some weakness, he has made a great achievement in Islamic modernism to answer humans problems.